ON TENSORS AND THE VOLUME ELEMENT OF LORENTZIAN MANIFOLD - Karagoz, Serpil (IJRDO -JOURNAL OF MATHEMATICS, 2024)
In this work, we give the relationship between the alterne tensor determinant which is the volume element of Lorentzian manifold and the symmetric tensor inner product on it.